Validation of Downy Mildew Resistance in Cucumber Germplasm Through Artificial Screening - Hegde, Vivek; SandeepKumar , G M; K R, Kavyashree; Sagar, Vidya; Dey, Shyam Sundar; Pandey, Chithra Devi; Gawade, Bharat H; Ranjan, Pragya (Current Horticulture, 2025)
The present study was conducted to validate downy mildew resistance in three promising cucumber accessions, IC527431, IC527400, and IC572024, through artificial inoculation at the greenhouse facility of ICAR-IIHR, Bengaluru, during 2024–25. These lines were previously identified through a multi-location trial conducted at New Delhi, Varanasi, and Bengaluru, India, from 2022–24. Three check varieties, Pusa Uday, Pusa Barkha, and Arka Veera were included to compare the performance of the selected genotypes. Thirty-five days after inoculation, the check varieties Pusa Uday (77.78% PDI) and Pusa Barkha (51.85% PDI) exhibited highly susceptible reactions. In contrast, only mild symptoms were observed on the leaves of IC572024, IC527431, and IC527400, with average Per cent Disease Index (PDI) values of 12.96, 15.74, and 29.63, respectively indicating resistant to moderately resistant responses. These germplasm lines appear promising as sources of resistance to downy mildew in cucumber and hold potential for use in the development of resistant cultivars.